73 THE NEW CHRONIC DISEASE MANAGEMENT PROGRAMME FOR GENERAL PRACTITIONERS: MAKING THE CASE FOR ITS REVISION TO INCLUDE DEMENTIA. (18th November 2021) - Pierce, M; Cahill, S
Abstract: Background: A significant component of the new contract for general practitioners is the chronic disease management programme (CDMP for GPs). Although dementia can be framed as a chronic disease, it was not included in this programme. Its exclusion raises a number of questions including: Should dementia be framed as a chronic disease? Is it feasible to include dementia in a future revised CDMP for GPs? What are the likely benefits and potential risks? Methods: This presentation focuses on two elements of a larger mixed-methods study, namely: (i) in-depth analysis of the CDMP for GPs, involving a review of the programme's three main components to test the feasibility of extending it to incorporate dementia; and (ii) qualitative content analysis of data from semi-structured interviews with 12 stakeholders whose expertise is in dementia, chronic disease or both. Both elements were informed by a literature review. Results: No consensus was found about whether dementia should be framed as a chronic disease. Results showed that it is feasible to extend the annual preventative programme of the CDMP for GPs to include additional modifiable dementia risk factors. While opportunistic case finding for identifying undiagnosed dementia cannot be recommended, a tool is available that would enable GPs identify people with dementia for enrolment on the structured treatment programme . Expected benefits from including dementia in the CDMP for GPs include integrated care pathways, better GP access and record-keeping and greater emphasis on primary and secondary prevention. Expected risks include excessive costs, caregiver burden, increased GP workload and sub-optimal care due to lack of specialist dementia training. Conclusion: There is a compelling case to support dementia risk reduction in the CDMP for GPs. However, the programme's current emphasis on self-management and rigidly planned visits could prove problematic for people with dementia and would need substantial revision.